(untitled) (Research, Society and Development, 2021)
Yogurt is a food fermented by characteristic microorganisms. Contains essential components for health, such as vitamins and minerals, protein, calcium, potassium, phosphorus, vitamins B6 and B12. Therefore, the objective of this study was to develop and characterize fermented products with probiotic potential added to purple grape jelly (Vitis vinífera L). For this purpose, three types of fermented yoghurt (S1) were prepared, composed only of the starter culture, (S2) fermented containing the starter culture and the purple grape jelly. For the probiotic formulation (S3), Lactobacillus acidophilus was added, the starter culture. and the purple grape jelly. The products were evaluated for humidity, titratable acidity, pH, lipid, lactose, ash, syneresis parameters, as well as viable bacterial cell counts and microbiological quality. It was observed that the elaborated yogurts met the physical-chemical and microbiological requirements established in the current Brazilian legislation, with lactic acid bacteria presenting values ​​higher than 107 CFU / mL, and the absence of total coliforms, the presence of molds and yeasts being within the value allowed by the legislation. . At the end, it was verified that the elaboration of probiotic fermented with red grape jelly can demonstrate a positive influence, emphasizing the need for more analyzes, in the industrial commercialization for dairy products that have functional properties, since it presents adequate physical- chemical and microbiological.